Love and other words - Lauren, Christina (Gallery Books, 2018)
Macy Sorensen works hard as a new pediatrics resident, plans a wedding to an older, financially secure man, and keeps her heart tucked away. When she runs into Elliot Petropoulos, the first and only love of her life, the careful bubble she's constructed begins to dissolve. As teenagers, Elliot and Macy spent lazy summers together in a house outside of San Francisco devouring books, sharing favorite words, and talking through their growing pains and triumphs. As adults, they have become strangers until their chance reunion. Will they overcome the past to revive a faith in the possibility of an all-consuming love?